Comparative trial of a novel botulinum neurotoxin type A versus onabotulinumtoxinA in the treatment of glabellar lines: A multicenter, randomized, double‐blind, active‐controlled study. (14th October 2014) - Won, Chong Hyun; Kim, Hyun Kyu; Kim, Beom Joon; Kang, Hoon; Hong, Joon Pio; Lee, Su‐Young; Kim, Chung‐Sei
Abstract A novel botulinum neurotoxin type A (DWP450; Daewoong Pharmaceutical, Seoul, Korea) has recently been introduced for the treatment of facial wrinkles. The efficacy of this agent has previously been demonstrated in an in vivo study using an electrophysiological protocol in a rat model. To compare the efficacy and safety of DWP450 with onabotulinumtoxinA (OBoNT) for use in the treatment of glabellar lines, we performed a multicenter, double‐blind, randomized, active‐controlled trial comparing DWP450 and OBoNT (Allergan Inc., Irvine, CA, USA). A total of 268 subjects with moderate to severe glabellar lines were randomized at a 1 : 1 ratio. Each patient received treatment with 20 U of study medication. Maximum frown responder rates at week 4 were measured to analyze the primary efficacy endpoint. To evaluate secondary efficacy endpoints, response rates were measured at weeks 8, 12, and 16, at maximum frown and rest. Specifically, responder rates at both maximum frown and at rest were assessed based on clinical photography. Subject degree of satisfaction and self‐assessed rate of response were also measured. Adverse events (AEs) were documented to evaluate safety. Responder rate by physician‐rating severity at maximal contraction at week 4 was 93.89% in the DWP450 group and 88.64% in OBoNT group. As the lower limit of the 97.5% one‐sided confidence interval (– 1.53%) surpassed the – 15% threshold, we determined that DWP450 was not inferior to OBoNT. For the secondary efficacy endpoint analyses, no significant differences were observed between the two groups for any variable at any point in time. The incidences of AEs were similar for the two groups. Most of AEs were considered mild. DWP450 and OBoNT were comparable in efficacy and safety in the treatment of glabellar lines.